2023
DOI: 10.3389/fpsyg.2023.1060543
|View full text |Cite
|
Sign up to set email alerts
|

Mental healthcare for young and adolescent LGBTQ+ individuals in the Indian subcontinent

Abstract: The coronavirus disease (COVID-19) pandemic has led to a significant change in the way healthcare is dispensed. During the pandemic, healthcare inequities were experienced by various sections of society, based on gender, ethnicity, and socioeconomic status. The LGBTQ individuals were also affected by this inequity. There is a lack of information on this topic especially in the developing countries. Hence this issue requires further exploration and understanding. Previous literature briefly explored the mental,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…The 79 included papers drew primarily from data collected in East Asia and the Pacific ( n = 28, 35.44%) [ 23 , 24 , 33 , 35 , 39 , 45 , 46 , 51 , 52 , 58 62 , 68 , 70 , 72 , 75 84 ], Sub-Saharan Africa ( n = 25, 31.65%) [ 26 – 31 , 38 , 41 , 43 , 44 , 50 , 63 , 66 , 71 , 85 – 95 ], and South Asia ( n = 20, 25.32%) [ 25 , 32 , 34 , 40 , 42 , 49 , 53 , 54 , 54 , 56 , 57 , 64 , 65 , 69 , 73 , 74 , 96 99 ] (see Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 79 included papers drew primarily from data collected in East Asia and the Pacific ( n = 28, 35.44%) [ 23 , 24 , 33 , 35 , 39 , 45 , 46 , 51 , 52 , 58 62 , 68 , 70 , 72 , 75 84 ], Sub-Saharan Africa ( n = 25, 31.65%) [ 26 – 31 , 38 , 41 , 43 , 44 , 50 , 63 , 66 , 71 , 85 – 95 ], and South Asia ( n = 20, 25.32%) [ 25 , 32 , 34 , 40 , 42 , 49 , 53 , 54 , 54 , 56 , 57 , 64 , 65 , 69 , 73 , 74 , 96 99 ] (see Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Only three publications drew from studies conducted in low-income countries, all in Uganda [ 48 , 86 , 88 ]. Seventy-three papers described studies conducted, at least in part, in lower-middle-income countries, with the most from India ( n = 12, 15.19%) [ 32 , 34 , 40 , 49 , 53 , 56 , 64 , 65 , 74 , 97 99 ], the Philippines ( n = 10, 12.66%) [ 23 , 35 , 58 62 , 68 , 75 , 81 ], and Vietnam ( n = 10, 12.66%) [ 24 , 33 , 39 , 46 , 67 , 70 , 72 , 77 , 82 , 84 ]. Three papers were global in scope [ 16 , 55 , 100 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LGBTQ+ youth, especially those from conservative or unsupportive family environments, often face homelessness or psychological distress due to societal rejection. Access to healthcare services, including mental health support tailored to the LGBTQ+ community, remains inadequate in many regions (Gaur et al, 2023).…”
Section: Influence Of Historical Legislation: Section 377 and The Sha...mentioning
confidence: 99%
“…Educational materials often have biased representations of LGBTQ+ patients, which may contribute to social stigma. 23 A systematic review revealed significant implicit bias among medical, dental and nursing students in their interactions with LGBTQ+ patients. 24 LGBTQ+ patients, in a recent study described their interactions with healthcare providers as transactional, and experienced a sense of power imbalance in the healthcare system.…”
Section: Disparities By Social Roles and Factorsmentioning
confidence: 99%